Numerical Modeling for Engineering Analysis and Designing of Optimum Support Systems for Headrace Tunnel - Sajjad Hussain; Zahid Ur Rehman; Noor Mohammad; Muhammad Tahir; Khan Shahzada; Sajjad Wali Khan; Muhammad Salman; Mujahid Khan; Akhtar Gul (Advances in Civil Engineering)
The empirical and numerical design approaches are considered very important in the viable and efficient design of support systems, stability analysis for tunnel, and underground excavations. In the present research work, the rock mass rating (RMR) and tunneling quality index (Q-system) were used as empirical methods for characterization of rock mass based on real-time geological and site geotechnical data and physical and strength properties of rock samples collected from the alignment of tunnel. The rock mass along the tunnel axis was classified into three geotechnical units (GU-1, GU-2, and GU-3). The support systems for each geotechnical unit were designed. The 2D elastoplastic finite-element method (FEM) was used for the analysis of rock mass behavior, in situ and redistribution stresses, plastic thickness around the tunnel, and performance of the design supports for the selection of optimum support system among RMR and Q supports for each geotechnical unit of tunnel. Based on results, Q support systems were found more effective for GU-1 and GU-2 as compared to RMR support systems and RMR support systems for GU-3 as compared to Q support systems.